2016
DOI: 10.1155/2016/8487378
|View full text |Cite
|
Sign up to set email alerts
|

Text Message Reminders Increase Appointment Adherence in a Pediatric Clinic: A Randomized Controlled Trial

Abstract: Background. High no-show rates can burden clinic productivity and affect patient care. Although multiple studies have shown that text messages improve appointment adherence, very little research has focused on low-income and predominantly African American populations in resident clinic settings. Objectives. To determine whether incorporating a text message reminder reduces the no-show rate at an urban, pediatric resident clinic. Methods. A randomized controlled trial was conducted at a tertiary level ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…There is a significant body of literature on text messaging as a means of, for instance, supporting people with chronic illness; [46][47][48] facilitating adherence and/or attendance; [49][50][51][52] conveying results of tests; 53 or sending health promotion messages. [54][55][56][57] Systematic reviews have indicated that text messaging can be effective in facilitating short-term behaviour and medication adherence in particular.…”
Section: Text Messaging and E-mailmentioning
confidence: 99%
“…There is a significant body of literature on text messaging as a means of, for instance, supporting people with chronic illness; [46][47][48] facilitating adherence and/or attendance; [49][50][51][52] conveying results of tests; 53 or sending health promotion messages. [54][55][56][57] Systematic reviews have indicated that text messaging can be effective in facilitating short-term behaviour and medication adherence in particular.…”
Section: Text Messaging and E-mailmentioning
confidence: 99%
“…This cannot happen if one has no phone and so may lead to loss to follow up. Mobile phone technologies (mHealth), specifically SMS reminders have improved patient outcomes in other health service delivery settings [3638] but were comparable to the standard of care for HIV retention in other settings [21,30]. It is however important to note that the level of interaction between provider and patient, and subset of activities under mHealth greatly determine the effectiveness of particular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile communications technology has the potential to enhance adherence to health care services by facilitating interactive and timely access to relevant information [26]. The short OJPHI message service (SMS) is one of the most widely used mobile communication method that is capable of sending and receiving text messages as a means of communication.…”
Section: Ojphimentioning
confidence: 99%
“…The short OJPHI message service (SMS) is one of the most widely used mobile communication method that is capable of sending and receiving text messages as a means of communication. SMS based services are now more attractive to service providers and users as a result of the recent mobile phone use penetration and the large scale adoption of the existing services by users [26].…”
Section: Ojphimentioning
confidence: 99%